Splitting the herd : a corral of odds and evens - Harris, Trudy, 1949- (Millbrook Press, 2008)
When Miss Emma's cows wander into Cowboy Kirby's pasture, he uses odd and even numbers to count and split the herd, not realizing his math mistake.